2017
DOI: 10.3389/fimmu.2017.00584
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immunity and Breast Milk

Abstract: Human milk is a dynamic source of nutrients and bioactive factors; unique in providing for the human infant’s optimal growth and development. The growing infant’s immune system has a number of developmental immune deficiencies placing the infant at increased risk of infection. This review focuses on how human milk directly contributes to the infant’s innate immunity. Remarkable new findings clarify the multifunctional nature of human milk bioactive components. New research techniques have expanded our understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
263
0
20

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(286 citation statements)
references
References 106 publications
(136 reference statements)
3
263
0
20
Order By: Relevance
“…Our findings are consistent with results of the recent study by Ahmadizar et al , which has shown that breastfeeding is associated with a decreased risk of asthma exacerbations in later childhood . These results are consistent with findings that breastfeeding may have immunomodulatory and anti‐infective antimicrobial effects, thereby impacting upon the risk of exacerbations (which are likely mostly virus‐induced) . Breast milk contains high levels of immunoglobulins, lactoferrin, cytokines and prebiotic structures that influence the development of immune system .…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are consistent with results of the recent study by Ahmadizar et al , which has shown that breastfeeding is associated with a decreased risk of asthma exacerbations in later childhood . These results are consistent with findings that breastfeeding may have immunomodulatory and anti‐infective antimicrobial effects, thereby impacting upon the risk of exacerbations (which are likely mostly virus‐induced) . Breast milk contains high levels of immunoglobulins, lactoferrin, cytokines and prebiotic structures that influence the development of immune system .…”
Section: Discussionsupporting
confidence: 93%
“…Em nosso estudo foi observado que crianças que receberam amamentação materna por mais de seis meses tiveram uma menor prevalência de infecções parasitárias quando comparadas às crianças que amamentaram por até seis meses ou menos. Segundo Cacho & Lawrence 27 , o leite materno protege as crianças contra infecções devido ao fato de apresentar compostos com ação antimicrobiana, anti-inflamatória, imunomoduladora, além de leucócitos. Devido à imaturidade do sistema imune, o recém-nascido é mais vulnerável às infecções, sendo fundamental a proteção conferida pela amamentação 28 .…”
Section: Variáveisunclassified
“…Devido à imaturidade do sistema imune, o recém-nascido é mais vulnerável às infecções, sendo fundamental a proteção conferida pela amamentação 28 . Substâncias imunológicas e fatores de crescimento presente no colostro e no leite materno protegem a mucosa intestinal contra a invasão de patógenos 24,27,28 e portanto, reduzem os riscos de infecção enteroparasitária.…”
Section: Variáveisunclassified
“…Evidence supports reduced childhood morbidity and mortality not only during the period of lactation but also beyond this period and into adulthood [20]. Facultative anaerobes create an anaerobic environment where obligate anaerobic bacteria such as Bifidobacterium species flourish.…”
Section: Establishment Of the Microbiome And The Relationship Betweenmentioning
confidence: 99%